A Global Fireball Observatory. (15th October 2020) - Devillepoix, H.A.R.; Cupák, M.; Bland, P.A.; Sansom, E.K.; Towner, M.C.; Howie, R.M.; Hartig, B.A.D.; Jansen-Sturgeon, T.; Shober, P.M.; Anderson, S.L.; Benedix, G.K.; Busan, D.; et al.
Abstract: The world's meteorite collections contain a very rich picture of what the early Solar System would have been made of, however the lack of spatial context with respect to their parent population for these samples is an issue. The asteroid population is equally as rich in surface mineralogies, and mapping these two populations (meteorites and asteroids) together is a major challenge for planetary science. Directly probing asteroids achieves this at a high cost. Observing meteorite falls and calculating their pre-atmospheric orbit on the other hand, is a cheaper way to approach the problem. The Global Fireball Observatory (GFO) collaboration was established in 2017 and brings together multiple institutions (from Australia, USA, Canada, Morocco, Saudi Arabia, the UK, and Argentina) to maximise the area for fireball observation time and therefore meteorite recoveries. The members have a choice to operate independently, but they can also choose to work in a fully collaborative manner with other GFO partners. This efficient approach leverages the experience gained from the Desert Fireball Network (DFN) pathfinder project in Australia. The state-of-the art technology (DFN camera systems and data reduction) and experience of the support teams is shared between all partners, freeing up time for science investigations and meteorite searching. With all networks combined together, the GFO collaboration already covers 0.6% of the Earth's surface for meteorite recovery as of mid-2019, and aims to reach 2% in the early 2020s. We estimate that after 5 years of operation, the GFO will have observed a fireball from virtually every meteorite type. This combined effort will bring new, fresh, extra-terrestrial material to the labs, yielding new insights about the formation of the Solar System. Highlights: A large international collaboration is being set up to observe meteorite falls on Earth, aiming 2% Earth coverage. The recovery of different types of fresh meteorites helps understanding the early Solar System. The orbital origins of meteorites also inform us about the hazard posed by larger Near-Earth Objects.